2003
DOI: 10.1046/j.1365-2842.2003.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

First night effect of an interocclusal appliance on nocturnal masticatory muscle activity

Abstract: The purpose of this study was to examine the effect of an interocclusal appliance on nocturnal masticatory muscle activities. Six healthy Japanese males (mean age: 26.8 years) participated in this study. Electromyographic (EMG) activities of the right anterior temporalis and masseter muscles were recorded using a portable EMG recording unit at night both with and without an interocclusal appliance. In both muscles, the maximal EMG activity and the number of bruxing events decreased significantly by wearing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 25 publications
1
27
0
7
Order By: Relevance
“…Several studies have been proposed to elucidate the splint action such as the modulation of neuromuscular function, relief of temporomandibular joints' loads and psychological effects (Hiyama et al, 2003). Glaros and Rao (1977) suggested that some studies had demonstrated changes in the masticatory muscular activity after the sear of OC wear in awaken patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been proposed to elucidate the splint action such as the modulation of neuromuscular function, relief of temporomandibular joints' loads and psychological effects (Hiyama et al, 2003). Glaros and Rao (1977) suggested that some studies had demonstrated changes in the masticatory muscular activity after the sear of OC wear in awaken patients.…”
Section: Introductionmentioning
confidence: 99%
“…Okeson 22 found that wearing soft occlusal splints increased bruxism, whereas, hard occlusal splints worn by the same subjects reduced nocturnal clenching and grinding behaviour. More recently, Hiyama et al 23 confirmed the observation of a reduction in nocturnal masticatory muscle activity for hard splints. Certainly, hypertrophy of the muscles of mastication principally masseter muscles is a feature of migraineurs with parafunctional 16 activity as are mandibular tori.…”
Section: Discussionmentioning
confidence: 86%
“…Occlusal splint treatment is still a common therapy in clinical treatment of splint [7], but it needs long-term therapy in order to have slow improvements in sleep bruxiam [8]. This study has focused on the treatment of a splint called "Yin Xinmin" splint.…”
Section: Discussionmentioning
confidence: 99%